2007
DOI: 10.1677/joe-06-0143
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone or dexamethasone regulates rat proopiomelanocortin transcription through Tpit/Pitx-responsive element in its promoter

Abstract: Tpit/Pitx-responsive element (Tpit/PitxRE), which binds transcription factors Tpit and Pitx1, confers cell-type specific expression of proopiomelanocortin (POMC) gene in pituitary corticotrops where the gene expression is mainly regulated by corticotropin-releasing hormone (CRH) and glucocorticoids (Gcs). CRH stimulates POMC gene expression, which is mediated by the accumulation of intracellular cAMP and requires binding of Nur factors to Nur-responsive element (NurRE). Gcs antagonize NurRE-dependent POMC gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…As shown in Fig 5A and 5B, DEX did not decrease Tpit and Pitx1 mRNA expression in time-dependent manners. This is consistent to the previous report by Murakami et al [27] which demonstrated that DEX did not suppress mRNA expression of Tpit and Pitx1 . These data indicate that the DEX-mediated Pomc transcription suppression may not be mediated via the decrease of Tpit and Pitx1 mRNA expression.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…As shown in Fig 5A and 5B, DEX did not decrease Tpit and Pitx1 mRNA expression in time-dependent manners. This is consistent to the previous report by Murakami et al [27] which demonstrated that DEX did not suppress mRNA expression of Tpit and Pitx1 . These data indicate that the DEX-mediated Pomc transcription suppression may not be mediated via the decrease of Tpit and Pitx1 mRNA expression.…”
Section: Resultssupporting
confidence: 94%
“…Reverse transcription mixtures were subjected to qPCR with KAPA SYBR FAST Universal 2x qPCR Master Mix (KAPA Biosystems) for primers of Pomc , NeuroD1 , Pan1 ( E47 ), Rb , and GAPDH using a CFX connect Real Time PCR thermal cycler (Bio-Rad, Hercules, CA). The following primer sequences were used: mouse Pomc (forward, ; reverse, ), mouse NeuroD1 (forward, ; reverse, ), mouse Pan1 ( E47 ) (forward, ; reverse, ), mouse Rb (forward, ; reverse, ), mouse Tpit (forward, ; reverse, ), mouse Pitx1 (forward, ; reverse, ) [27], mouse Nur77 (forward, ; reverse, ) [31], mouse Nurr1 (forward, ; reverse, ) [32], mouse GAPDH (forward, ; reverse, ), rat Pomc (forward, ; reverse, ) [33] and rat GAPDH (forward, ; reverse, ) [34]. Reactions were incubated at 95°C for 1 min and then amplified using temperature parameters of 95°C for 15 sec; 60°C for 10 sec; 72°C for 20 sec.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfected cells were washed in phosphate-buffered saline (PBS (−)), and lysed with the reporter lysis buffer provided in a DualLuciferase Reporter Assay System (Promega) according to the manufacturer's instructions and our previous study (Murakami et al, 2007). The lysates were assayed for luciferase activity using a T-20/20 Luminometer (Promega).…”
Section: Reporter Assaymentioning
confidence: 99%
“…This compound competitively inhibits the binding of calmodulin to CaMKII by interacting with the calmodulin binding site and thus inactivates the enzyme (Hidaka and Yokokura 1996). KN-62 was applied at 10 μM, a concentration widely used in different systems, including rat anterior pituitary cells, to inhibit specifically CAMKII activity (Cui et al 1996;Roberson et al 2005;Murakami et al 2007). As shown in Fig.…”
Section: +mentioning
confidence: 99%